Lipid diffusion in giant unilamellar vesicles is more than 2 times faster than in supported phospholipid bilayers under identical conditions - Przybylo, Magdalena; Sýkora, Jan; Humpolíckova, Jana; Benda, Ales; Zan, Anna; Hof, Martin (Langmuir, 2006)
The lateral diffusion coefficients of a BODIPY tail-labeled lipid in two model systems, namely, free-standing giant unilamellar vesicles (GUVs) and supported phospholipid bilayers (SPBs), were determined by fluorescence correlation spectroscopy (FCS) using the Z-scan approach. For the first time, the performed measurements on 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC) bilayers maintain exactly the same experimental conditions for both systems, which allows for a quantitative comparison of lipid diffusion in these two commonly used model membranes. The results obtained revealed that the lipid mobility in free-standing bilayers (D=7.8+/-0.8 microm2 s-1) is significantly higher than in the bilayer created on the solid support (mica) (D=3.1+/-0.3 microm2 s-1).
Keywords: časové faktory; Lipid Bilayers; Time Factors; fosfatidylcholiny; lipidové dvojvrstvy; difuze; Phosphatidylcholines; Diffusion